1991
DOI: 10.1111/j.1476-5381.1991.tb09797.x
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of functional activity of human pulmonary arteries after cryopreservation

Abstract: 1 Human intrapulmonary arteries have been investigated in vitro in fresh tissue or after storage at -190'C in foetal calf serum containing 1.8 M dimethyl sulphoxide. 2 After cryopreservation of the arteries, maximal contractile force was reduced to 76%. This was assessed by the responses (in g) to 10 nm of the thromboxane analogue, U 46619. 3 Constricting agonists such as noradrenaline, 5-hydroxytryptamine, histamine and U 46619 stimulated fresh and frozen/thawed arteries producing pD2 values similar to the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 19 publications
(13 reference statements)
0
10
1
Order By: Relevance
“…These authors observed contractile responses similar to those of the present investigation. However, in the present investigation, the maximal endothelialdependent relaxation was similar between cryopreserved and fresh arteries (approximately 90% of the induced contraction) and higher than the 30% to 50% reported by Müller-Schweinitzer et al The two main reasons for these differences can be ascribed to a variation in susceptibility to the cryopreservation procedure, which may vary from tissue to tissue, 6,10,18,19 and to methodologic differences in the cooling process. We used a computerized program that was designed and is used in our institution to ensure a constant slow rate of 0.7˚C per minute, in contrast to the manual cooling rate.…”
Section: A B Ccontrasting
confidence: 60%
“…These authors observed contractile responses similar to those of the present investigation. However, in the present investigation, the maximal endothelialdependent relaxation was similar between cryopreserved and fresh arteries (approximately 90% of the induced contraction) and higher than the 30% to 50% reported by Müller-Schweinitzer et al The two main reasons for these differences can be ascribed to a variation in susceptibility to the cryopreservation procedure, which may vary from tissue to tissue, 6,10,18,19 and to methodologic differences in the cooling process. We used a computerized program that was designed and is used in our institution to ensure a constant slow rate of 0.7˚C per minute, in contrast to the manual cooling rate.…”
Section: A B Ccontrasting
confidence: 60%
“…This concentration is expected to maintain cell viability within the tissue. Evidence has shown that after thawing, both biochemical and functional activities of arterial tissue cryopreserved at low temperatures in Krebs solution containing 1.8 M of DMSO were comparable to fresh tissues [41].…”
Section: Discussionmentioning
confidence: 97%
“…The contractions observed with U46619 (stable thromboxane A 2 mimetic) and their inhibition by the selective TP‐antagonists (GR32191B, Lumley et al ., 1989 and BAY u3405, McKenniff et al ., 1991) suggest the presence of a TP‐receptor in human pulmonary veins. These results have not previously been reported although the TP‐receptor has been frequently described in human pulmonary arteries (Maddox et al ., 1985; Sjoberg & Steen, 1989; Lumley et al ., 1989; Norel et al ., 1991; Ellis & Muller‐Schweinitzer, 1991; Qian et al ., 1994; Jino et al ., 1996). Pharmacological studies as well as investigations using molecular biology have suggested heterogeneity among thromboxane receptors (Lumley et al ., 1989; Tymkewycz et al ., 1991; Furci et al ., 1991; Pierce & Regan, 1998).…”
Section: Discussionmentioning
confidence: 99%